Company Stock Valuation Of Pt. Waskita Karya Tbk And The Impact Of Delayed Bonds Payment - Firman Arief; Subiakto Sukarno (Journal Research of Social Science, Economics, and Management, 2023)
The construction industry has demonstrated resilience during the pandemic, becoming a global economic engine. Indonesia's PT Waskita Karya Tbk, a state-owned construction company, reported negative financial performance in its annual report, indicating a decline in revenues. As a public corporation, the company must maintain excellent financial performance and offer opportunities for shareholders. The movement of SOE's Construction shares with the code WSKT has also experienced a downward trend. Based on the dynamics of the business environment, the purpose of this research is to gain a deeper understanding of the Indonesian construction industry to identify Waskita Karya's challenges and opportunities. In addition, the study will determine the company's intrinsic and relative value if it defaults on its debts. The research will compute the company's value using the discounted cash flow (DCF) method and comparable companies. The study analyzes the impact of bond payment delays on Waskita Karya's financial performance, examining how these delays affect cash flow, liquidity, and overall financial health. The study focuses on the company stock valuation of PT. Waskita Karya Tbk and the impact caused by bond payment delays. The findings provide valuable insights for investors, stakeholders, and financial analysts, helping them make informed decisions about their investment in Waskita Karya’s and better understand associated risks and opportunities. In conclusion, using the discounted cash flow analysis method, the implied value per share is IDR 550.22.